(untitled) (Scientific journal of the Fergana State University, 2024)
Linguistic-pedagogical features of increasing students’ vocabulary depend on the system or set of exercises for successful acquisition of knowledge, skills and competences in all types of speech activities, as well as on the formation of communicative and other competencies in the process of language teaching. Linguistic-pedagogical features of increasing students’ vocabulary, keeping a dictionary or diary of new words, performing exercises are put forward in the article.